Legislar pela exclusão social: um estudo da atividade legislativa sobre cumprimento da pena de 1984 a 2011 - Ferreira, Carolina Cutrupi (2011)
The main objective of this dissertation is to understand the Legislative activities and your interaction among Judiciary and Executive in terms of enforcement of criminal sanction. The considered assumption is that the process of creation of laws about sanction management in Brazil is recurrent the selection of prisons sentences, and the management way created by LEP (Law of Penal Execution) is subject of few proposals of legislative reform. This study includes an empirical research of legislative proposals presented to National Congress between 1984 and 2011 related to the enforcement of criminal sanction. The second chapter of the dissertation contains a quantitative analysis of these proposals, through the systematization of general data (type of proposition, length of the procedure for approval, federal state of origin and author) to identify, when possible, the increase or decrease trend of social exclusion through the use of more or less frequence of imprisonment. The qualitative analysis focus on the concepts of management of criminal sanction and individualization of punishment. The third chapter introduces the concept of management of criminal sanction, review of legislative historical creation of legal degree to accomplishment of sanction until the creation of LEP in 1984, and reinforces a qualitative study of task divisions about accomplishment of sanction from an empirical material. The fourth chapter introduces the idea of individualization of sanction, as approached in a judicial activity, which interacts in a dynamic and constant way with legislative and administrative activities, especially while the accomplishment of prison sentencing. From this concept, new legislative proposals present a new arrangement of distribution of tasks among the three powers regarding enforcement of criminal sanction. The conclusion of this dissertation is that the creation process of criminal laws in Brazil recognizes the use of freedom private sanction, considering the extension of minimum prison quorum or the extinction of subjective rights, in a situation that the judge has no many possibilities to actuate in case.